BOGGED DOWN IN THE PAST - Shovkovyy, Oleg (PEOPLE: International Journal of Social Sciences, 2019)
Grounded on almost eight months of insider’s observations research data suggest, that many immigrants, mainly because of their limited communications with natives and without proper government assistance, are unable to break out from the pursuing past and instead, they are joining existent or forming their networks. It is also the case, that very often, those immigrants’ communities, live their own lives which, in many respects, differ from the life of the host country. Findings allow the author to make a bold assumption about the harmful role of Russian-speaking communities on processes of integration of immigrants into the host society. Those communities not only do not contribute to the restructuring of behavioral and thinking patterns of immigrants but, support the opposite. The ‘Russian’ church, for example, while being a strong unifying factor for Russian-speakers abroad, instead of using its authority to help integration, is the first to resist and to promote the foreign to host country mode of life and, is not interested in changing its status quo. To ensure better integration and assimilation of immigrants into host societies, the author suggests, that the governments must be more proactive in organizing lives of those foreign speaking communities and diasporas whereas today, all this is left to chance.